Pembinaan Komunitas dalam Meningkatkan Kualitas Pendidikan di Desa Tertinggal - Noviandari, Hanifah (STAI Terpadu Yogyakarta, 2024)
This service aims to analyze community empowerment in improving the quality of education in Klepu Village, Ponorogo, which is one of the underdeveloped villages in the region. The research questions address: (1) how the quality of education in Klepu Village is before and after community empowerment, (2) the challenges faced by the community in participating in the empowerment program, and (3) the effectiveness of the empowerment program in improving the skills of educators and students. The method used is a participatory approach involving training, seminars, and workshops that engage educators, students, and the local community. The analysis results show that community empowerment has successfully improved the quality of education in Klepu Village, reflected in the improved academic performance of students, enhanced competencies of educators, and increased parental involvement. The main challenges faced were limited time and distance, but these were overcome through a more flexible approach. The implications of this study highlight the importance of continuous empowerment and community-based approaches to improving education quality in underdeveloped villages.